(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
The Hoek-Brown (H-B) criterion is one of the most commonly used rock failure criteria in recent years. This criterion includes a constant parameter called mi which is a fundamental parameter for estimating rock strength. Due to the importance of the mi parameter in the H-B criterion, it is necessary to conduct comprehensive studies on various aspects of the effect of this parameter on the behavior of rocks. Therefore, in this study, using numerical simulation of the Triaxial Compressive Strength (TCS) tests in PFC-2D code, the effects of microscopic properties of different rocks on the H-B parameter mi have been studied. Based on the results of this study, it was found that the effects of micro-parameters on the H-B parameter mi can be different depending on the type of rock, however this parameter has an inverse relationship to the micro-parameters of bond tensile strength and bond fraction of the rocks. Also, the mi parameter increases with an increase in the micro-parameters of the friction coefficient, the friction angle, the particle contact modulus, and the contact stiffness ratio of rocks.